Characterisation of Shigella Spa33 and Thermotoga FliM/N reveals a new model for C‐ring assembly in T3SS. Issue 4 (23rd December 2015) - McDowell, Melanie A.; Marcoux, Julien; McVicker, Gareth; Johnson, Steven; Fong, Yu Hang; Stevens, Rebecca; Bowman, Lesley A. H.; Degiacomi, Matteo T.; Yan, Jun; Wise, Adam; Friede, Miriam E.; Benesch, Justin L. P.; et al.
Summary: Flagellar type III secretion systems (T3SS) contain an essential cytoplasmic‐ring (C‐ring) largely composed of two proteins FliM and FliN, whereas an analogous substructure for the closely related non‐flagellar (NF) T3SS has not been observed in situ . We show that the spa33 gene encoding the putative NF‐T3SS C‐ring component in S higella flexneri is alternatively translated to produce both full‐length (Spa33‐FL) and a short variant (Spa33‐C), with both required for secretion. They associate in a 1:2 complex (Spa33‐FL/C2 ) that further oligomerises into elongated arrays in vitro . The structure of Spa33‐C2 and identification of an unexpected intramolecular pseudodimer in Spa33‐FL reveal a molecular model for their higher order assembly within NF‐T3SS. Spa33‐FL and Spa33‐C are identified as functional counterparts of a FliM–FliN fusion and free FliN respectively. Furthermore, we show that T hermotoga maritima  FliM and FliN form a 1:3 complex structurally equivalent to Spa33‐FL/C2, allowing us to propose a unified model for C‐ring assembly by NF‐T3SS and flagellar‐T3SS. Abstract : We show that the gene encoding the putative NF‐T3SS C‐ring component in Shigella flexneri is alternatively translated to generate full‐length and short forms, both required for secretion. They form a 1:2 complex that oligomerises into elongated arrays. Identification of an intramolecular‐pseudodimer leads to a molecular model for their higher order assembly. We also show that the flagellar C‐ring is built from a structurally equivalent 1:3 complex leading to a unified model for C‐ring assembly.